The Influence Of Capital Structure, Company Size And Profitability On Company Value On Registered Insurance Companies On Bei 2018 – 2022 - Rida Bella Putri Cindi Hutabarat; Patar Marbun; Wan Rizca Amelia (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to determine (1) the Effect of Capital Structure on Company Value (2) The Effect of Company Size on Company Value (3) The Effect of Profitability on Company Value This study uses quantitative methods with a sample of 5 companies taken from the Indonesian Stock Exchange. The data analysis technique uses multiple linear regression tests. The results of this study show that Capital Structure (X1) has a positive and significant influence on Company Value (Y) as proven through the calculated t value of 5.057 > t table 1.706; Company Size (X2) has no positive and insignificant influence on Company Value (Y) proven through t count 1.248 < 1.706; Profitability (X3) does not have a positive and insignificant influence on Company Value (Y) proven through the calculated t value of -1.534 < t table 1.706 there is a significant influence between the influence of Capital Structure, Company Size and Profitability on Company Value . What is seen through F calculate > F table where the value is 13.030 and the significance value is 0.000 meaning together (Simultaneous)